Effects of diabetes mellitus on left atrial volume and functions in normotensive patients without symptomatic cardiovascular disease - KEPEZ, ALPER; ATAŞ, HALİL; TİGEN, MUSTAFA KÜRŞAT (ELSEVIER SCIENCE INC, 2014)
Purpose: Left atrial (LA) size has been shown to be a predictor of adverse cardiovascular outcomes. The aim of the study was to evaluate the direct effect of diabetes mellitus (DM) on left atrial volume and phasic functions by using real-time three-dimensional echocardiography (RT3DE) in a population of patients free of symptomatic cardiovascular disease and hypertension. Methods: Comprehensive transthoracic echocardiographic examination was performed on 40 consecutive patients with DM (20 male, age: 50.5 +/- 7.3 years) and 40 healthy controls (20 male, age: 48.4 +/- 6.7 years). In addition to conventional 2D echocardiographic measurements RT3DE was performed to assess LA volumes and phasic functions. Results: There were no significant difference between groups regarding parameters reflecting LV systolic function as LV diameters and ejection fraction. However, regarding parameters reflecting LV diastolic function; transmitral deceleration time and E/E' ratio values were significantly higher and majority of early diastolic tissue Doppler velocity values were significantly lower in diabetic patients compared with controls. RT3DE demonstrated significantly higher LA maximum and minimum volumes for diabetic patients compared with controls (40.9 +/- 11.9 vs 34.6 +/- 9.3 mL, p: 0.009 and 15.6 +/- 5.9 vs 11.9 +/- 4.6 mL, p: 0.002, consecutively). LA total emptying fraction (TEF), expansion index (El) and active emptying fraction (AEF) were found to be significantly lower in diabetics reflecting depressed LA reservoir and pump functions. There was no significant difference between groups regarding passive emptying fraction (PEF) which is assumed to be a marker of left atrial conduit function. Conclusion: Patients with type 2 diabetes mellitus were found to have increased LA volume and impaired atrial compliance and contractility. Evaluation of asymptomatic diabetic patients by using RT3DE atrial volume analysis may facilitate recognition of subtle myocardial alterations related with type 2 diabetes. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Diabetes mellitus; Left atrial volume analysis; Real time 3 dimensional echocardiography; Atrial compliance; Atrial contractility; TIME 3-DIMENSIONAL ECHOCARDIOGRAPHY; VENTRICULAR DIASTOLIC FUNCTION; SIZE; DYSFUNCTION; DIAMETER; STROKE; RISK